Upaya Satuan Narkoba Polrestabes Medan Dalam Menanggulangi Tindak Pidana Narkotika Melalui Aplikasi “Polisi Kita” - Nur Istiono; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
Abstract. In an effort to combat drug offenses by the Indonesian National Police (Polri), the Medan Polrestabes has launched a mobile application called "Our Police". The application is in response to the development of information technology and the high number of mobile users by the public. So that the existence of these applications is expected to minimize crimes that occur in the community, including illicit drug trafficking. Basically, for the community users of the application can easily report the illicit circulation of narcotics to Medan Polrestabes Officers to be forwarded to officers in the field to check the truth of the report. The use of the "Police Us" application is Polri's service to the community based on technology and knowledge (Technology and Knowledge Based). All units and units in the Medan Polrestabes are as much as possible in using technology and information in accordance with the demands of their duties. The "Our Police" application launched by the Medan Polrestabes is still something new. Therefore there are still many problems that arise in their use.   Keywords :     narcotics, medan polrestabes,  application of “Polisi Kita”.